2003
DOI: 10.4141/s03-007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of trace metals in Podzols of northern forest ecosystems: Sampling implications

Abstract: . 2003. Spatial variability of trace metals in Podzols of nothern forest ecosystems: Sampling implications. Can. J. Soil Sci. 83: 581-587. The concentrations of metals in soils are spatially heterogeneous and soil sampling carried out when studying metals in forest ecosystems is often inadequate. We examined the spatial variability of Cd, Cu, Mn, Ni, Pb and Zn in northern forest ecosystems on a transect with distance from two point source emitters with the goal of providing basic information about the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The trace metals within the soils at the six sampling sites were studied extensively by MacDonald and Hendershot. 40 Overall, they found that along the transect from the INCO nickel smelter (Sudbury), both copper and nickel were elevated in the soil, with the concentrations of total metal and exchangeable metal decreasing with distance away from the smelter. The site closest to the nickel smelter (S-1) was the only site to have been treated with remedial applications of CaCO 3 , which was used to raise the soil pH.…”
Section: Soil Metal Contentmentioning
confidence: 96%
See 2 more Smart Citations
“…The trace metals within the soils at the six sampling sites were studied extensively by MacDonald and Hendershot. 40 Overall, they found that along the transect from the INCO nickel smelter (Sudbury), both copper and nickel were elevated in the soil, with the concentrations of total metal and exchangeable metal decreasing with distance away from the smelter. The site closest to the nickel smelter (S-1) was the only site to have been treated with remedial applications of CaCO 3 , which was used to raise the soil pH.…”
Section: Soil Metal Contentmentioning
confidence: 96%
“…Whereas the concentrations of both total and exchangeable copper and nickel in the soil increased with proximity to the nickel smelter near Sudbury, 40 only the elevated nickel was detected in the tree rings ( Fig. 4).…”
Section: Sudburymentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining a representative field sample presents specific problems which, if ignored, may render all subsequent analytical work worthless [5]. The analytical significance that can be associated with spatial heterogeneity in metal distribution is large as recently demonstrated for forest ecosystems [6]. Analytical uncertainty generally develops from inadequate soil sampling strategies.…”
mentioning
confidence: 99%
“…One to two F, H or FH samples and one podzolic B sample in each plot were selected randomly for exchangeable H + analysis. The study in Rouyn is also part of a larger study investigating trace metal contamination in soils from anthropogenic point source emitters (MacDonald and Hendershot 2003).…”
mentioning
confidence: 99%